Respiratory syncytial virus epidemiology in Turkey - (:unkn) unknown (My University, 2005)
Respiratory syncytial virus (RSV) is the leading cause of lower respiratory tract infections in infants and young children worldwide. This study was conducted to determine the prevalence of RSV among high-risk children admitted with respiratory symptoms in a developing country. This is a multicenter study conducted among children less than 24 months of age and admitted to the hospital with respiratory symptoms. The inclusion criteria included: lower respiratory tract symptoms on admission, gestational age less than 35 weeks, and admission age less than six months, or children less than 24 months of age with a diagnosis of bronchopulmonary dysplasia requiring medical treatment or intervention during the last six months or with an uncorrected congenital heart disease (other than patent ductus arteriosus). Nasopharyngeal samples were obtained with one of the three standard methods: nasopharyngeal aspirate, nasopharyngeal wash or nasopharyngeal swab. RSV antigen was determined by enzyme immunoassay using Abbott TESTPACK RSV (No. 8100/2027-16). Statistical analysis was performed using Student's t-test and chi-square test. In this study, 332 children (135 females, 40.7%; 197 males, 59.3%) were included, and the nasopharyngeal specimens of 98 (29.5%) children were determined to be RSV-positive. There were no differences in sex, age of gestation, age of admission, family education, number of siblings and smoking at home for RSV-positive and -negative cases. Furthermore, underlying disease and duration of hospital and intensive care unit stay were similar among groups. Only otitis media was more common among RSV-positive cases. No fatality at hospital was recorded. Frozen samples revealed more negative results. Most cases presented during winter and the number of RSV-positive cases was higher in cold and economically poor areas. Premature children and children with underlying medical con dition acquire RSV irrespective of other sociodemographic risk factors, and most of them are hospitalized. Thus, an RSV vaccine seems the most effective mode of protection to decrease morbidity and mortality.
Keywords: Epidemiology; Respiratory syncytial virus